Novel shunt modification with an adjustable stent‐embedded "fenestrated" septal occluder in a patient with pulmonary hypertension. Issue 7 (6th March 2019) - Yadlapati, Ajay; Wax, David; Rich, Stuart; Ricciardi, Mark J.
Abstract: A 60‐year‐old woman with progressive dyspnea and cyanosis, O2‐dependent pulmonary hypertension despite optimal medical therapy and remote atrial septostomy presented with worsening cyanosis and right‐to‐left shunting. The creation of a "fenestrated" ASD closure device with the insertion of a peripheral stent through an AMPLATZER™ ASD closure device was deployed to minimize right to left shunting and allow for enlargement of the shunt if needed. This case demonstrates the benefit of diminishing a right to left shunt with a self‐fabricated fenestrated AMPLATZER device to improve symptoms in pulmonary hypertension patients with a pre‐existing ASD.